Efficiency of Protection of Guinea Pigs against Infection with Bacillus anthracis Spores by Passive Immunization - Kobiler, David (American Society for Microbiology, 2002)
The efficacy of passive immunization as a postexposure prophylactic measure for treatment of guinea pigs intranasally infected with Bacillus anthracis spores was evaluated. Antisera directed either against the lethal toxin components (PA or LF) or against a toxinogenic strain (Sterne) were used for this evaluation. All antisera exhibited high enzyme-linked immunosorbent assay titers against the corresponding antigens, high titers of neutralization of cytotoxicity activity in an in vitro mouse macrophages cell line (J774A.1), as well as in vivo neutralization of toxicity when administered either directly to Fisher rats prior to challenge with the lethal toxin or after incubation with the lethal toxin. In these tests, anti-LF antiserum exhibited the highest neutralization efficiency, followed by anti-Sterne and anti-PA. The time dependence and antibody dose necessary for conferring postexposure protection by the various antibodies of guinea pigs infected with 25 50% lethal doses of Vollum spores was examined. Rabbit anti-PA serum was found to be the most effective. Intraperitoneal injections of anti-PA serum given 24 h postinfection protected 90% of the infected animals, whereas anti-Sterne and anti-LF were less effective. These results further emphasizes the importance of anti-PA antibodies in conferring protection against B. anthracis infection and demonstrated the ability of such antibodies to be effectively applied as an efficient postexposure treatment against anthrax disease.